Adaptation and validation of the capacity scale for informal caregivers of elderly stroke patients to be used in Brazil - Dal Pizzol, Fernanda Laís Fengler (2020)
Background and Purpose: The Portuguese instrument for informal caregivers’ skillsproviding care of aged people after a stroke (ECPICID-AVC) evaluates the capaci-ties that informal caregivers must have for supporting aged stroke survivors. The purpose was to adapt and validate the ECPICID-AVC to be used in Brazil. Methods: A methodological study was conducted. Results: The terms with the lowest degreeof comprehension were adapted. The factor analysis suggested the exclusion of threeitems and that the remaining be grouped into six domains. The factor loadings variedfrom 0.525 to 0.924. The internal intra-assessor consistency was satisfactory (ICC =0.94, CI 95%). Total reliability was considered excellent (Cronbach’s alpha = 0.914). Conclusions: The ECPICID-AVC is considered appropriate for using in Brazil.